THE APPLICATION OF BEHAVIORISTIC THEORY IN THE 2013 CURRICULUM LEARNING TO SHAPE THE PRINCIPLES OF STUDENTS' CHARACTERS - Nasrallah Nasrallah; Bahaking Rama; Ulfiani Rahman (JICSA : Journal of Islamic Civilization in Southeast Asian, 2022)
The purpose of this study is to describe the application of behavioristic theory in the learning of morality in the 2013 curriculum at the elementary school level. In addition, to reveal the implications of behavioristic theory in learning morality in the 2013 curriculum to shape the morals of elementary school students. This type of research is classified as library research with an interpretative text approach. Data were collected by quoting, adapting, and analyzing using data analysis techniques using the Miles and Huberman model of representative literature and having relevance to the problem discussed, then interpreting the data so that it becomes a conclusion that is considered to answer the problem formulation. The results of the study indicate that there are two main implications, namely: educators utilize preliminary and closing activities of learning as a means to shape the morals of students, and educators cooperate with various components of education staff in schools to form attitudes that lead to moral formation, including: a. ) condition students in an environment that allows the formation of morals, b) create programs that allow students to learn to implement concept learning into practice, c) provide examples to students in the school environment; and d) make a moral commitment to students.